TRADE IN WEST AFRICA : THE TOWN OF FADA N’GOURMA - (:unkn) unknown (My University, 2020)
TRADE IN WEST AFRICA: THE TOWN OF FADA N’GOURMAAbstract:The urban agglomeration of Fada N’Gourma in the eastern region of Burkina Faso is located at thecrossroads of several countries in West Africa. It covers an area of 350 km², with a population ofapproximately 66,173 inhabitants in 2019 (INSD-Est, 1996-2006. p. 222; Projection I. DAHANI, 2020).This city hosted its first market between 1395 to 1439. The people who lived there carried out tradewhich was subsequently connected with those of West Africa. This market later became the main one inthe city. The commercial exchanges of the pre-colonial period and the marketing circuits that were builtin West Africa, allowed Fada N’Gourma to become a transit hub. The present survey is essentially builton field research by collecting primary data. It aims to present the city of Fada N’Gourma in the tradein West Africa of the pre-colonial, colonial and post-colonial periods. Thus, an examination of trade inWest Africa shows that this city is mainly a transit point for trade in West Africa from the pre-colonialperiod to the post-colonial period.
Keywords: African Research